Follow-up of blood glucose distribution characteristics in a health examination population in Chengdu from 2010 to 2016. Issue 8 (February 2018) - Wang, Yuting; Xu, Wangdong; Zhang, Qiongying; Bao, Ting; Yang, Hanwei; Huang, Wenxia; Tang, Huairong
Abstract : Abstract: The worldwide prevalence and incidence of diabetes and obesity are increasing in pandemic proportions. Thus, regular health examination is an important way for early detection of diabetes and glucose intolerance. The present study aims to detect the blood glucose distribution characteristics of the participants in the Health Examination Center at West China Hospital, Sichuan University from 2010 to 2016. A prospective cohort included 9168 Chinese participants, aged 18 years or more, who had available information on fasting blood glucose concentrations at the start of the study (2010). Examination surveys were conducted every year from 2010 to 2016. Cases having serum level of fasting blood glucose between 2.2 and 6.1 mmol/L were considered as normality, while serum level of fasting blood glucose < 2.2 or higher than 6.2 mmol/L were considered as abnormality. The percentage of participants having normal level of glucose was gradually reduced both in males and females from 2010 to 2016, by which the percentage of males having normal level of glucose was significantly lower than that in females. Moreover, the mean level of glucose was significantly increased from 2010 to 2016 both in males and females overall, and the mean level of glucose was higher in males compared with that in females every year. Furthermore, we showed that the level of glucose was gradually increased year by year in each age group, and the level of glucose was higher in aged cases compared with the young population. The study population in the current study showed higher levels of glucose with ages increasing, and males indicated higher expression of glucose than that in females. Some preventive action may be adopted early and more attention can be paid to this health-examination population. Abstract : Supplemental Digital Content is available in the text